Relação entre os componentes da biodiversidade: diversidade filogenética, funcional e taxonômica de taxocenoses de lagartos do cerrado brasileiro - Peixoto, Gabriela Marques (2014)
Estimates of phylogenetic and functional diversity are proposed as a promising way of explaining the role of interactions between species and the functioning of ecosystems. In this study we evaluated how the functional structure of the different assemblages of Brazilian savannah lizards is related to taxonomic and phylogenetic diversity. For this, we evaluated information about 5520 individuals of 50 species, at twenty sampling sites, located in both continuous Cerrado and enclaves of Amazon Savannah. We estimate species richness and taxonomic diversity through the Simpson Index. The functional diversity was obtained through traits related to morphometry and ecological aspects of each species. Phylogenetic diversity was based on recent phylogenies for Brazilian lizards. Our results revealed that phylogenetic diversity and species richness were positively related to functional diversity, which did not occur with the index of taxonomic diversity. Most of the functional traits were conserved within the lineages, and assemblages were structured either in aggregate (influence of environmental filters) or functionally dispersed (limiting similarity). We conclude that suppression of species of phylogenetically distinct lizards within the assemblages leads to loss of functional role, which may directly affect ecosystem processes. And what data regarding the phylogenetic aspects, or the species richness itself, can be good substitutes to infer about the functional information that influences the assembly rules of Cerrado lizard assemblages.